MODERN APPROACHES TO NEUROPROTECTION IN TRAUMATIC BRAIN INJURIES, CEREBROVASCULAR DISEASES, AND COGNITIVE IMPAIRMENTS FOLLOWING ANTITUMOR THERAPY - Hladkykh, Fedir; Liadova, Tetyana; Matvieienko, Mariia; Karafulidi, Olha; Zhuchenko, Pavlo (Eastern Ukrainian Medical Journal, 2025)
Background. With the increase in life expectancy, the number of patients with neurodegenerative diseases, particularly dementia, is rising. Concurrently, improving survival rates in cancer patients is accompanied by chemotherapy side effects, including cognitive impairments. Approximately 70% of patients after chemotherapy experience memory, attention, and multitasking problems, significantly affecting their quality of life.Objective of the study was to characterize contemporary approaches to neuroprotection in traumatic brain injuries, cerebrovascular diseases, and cognitive impairments following oncological treatment.Materials and Methods. Publications were selected from PubMed, Clinical Key Elsevier, Cochrane Library, eBook Business Collection, and Google Scholar, focusing on neuroprotection strategies for traumatic brain injury, cerebrovascular diseases, and cognitive impairments after cancer therapy. The review was prepared following PRISMA guidelines.Results. Neuroprotection in neurodegenerative and cerebrovascular diseases focuses on reducing oxidative stress, improving mitochondrial function, regulating excitotoxicity, and controlling neuroinflammation. A comprehensive approach that considers the neurovascular unit helps develop new therapeutic strategies for brain protection. Chemotherapy induces cognitive impairments through microglia activation, oxidative stress, and changes in cerebrovascular function. Psychostimulants, antidepressants, and anti-inflammatory drugs may improve cognitive functions, though their effectiveness requires further research. Combined strategies, including physical activity, cognitive-behavioral therapy, and pharmacotherapy, have shown potential for improving cognitive recovery after cancer treatment.Conclusions. Neurodegenerative diseases, ischemic stroke, and traumatic brain injury demand new therapeutic strategies. Cognitive impairments following chemotherapy require an integrated approach, combining psychopharmacology, cognitive-behavioral therapy, and physical activity.